Analisa Metode Pengukuran Kinerja Perusahaan - Hayatul Millah (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2018)
The main purpose of the company (management) is basically "stockholder wealth maximization that is by maximizing the market value of the company's stock" Based on these objectives, management will optimize its performance in order to show the credibility of the company in generating profit in the eyes of investors or stockholders. Measurement of company performance can be grouped into two, that is measurement of non financial performance (nonfinancial performance measurement) and measurement of financial performance (financial performance measurement). profit is a measuring tool to assess the performance of the company in a period, so that investors and shareholders are very focused on profit information without seeing the procedure of corporate profits.